THE TRANSLATION OF PERSONAL NAMES IN CHILDREN'S LITERATURE: THE CASE OF PROTAGONISTS (Journal of the College of Basic Education, 2022)
ABSTRACT: One of the challenging aspects in translation is the translation of personal names (PN(s) henceforth) in various significations referring to age, sex, geographical background, history, cultural indications, definite meaning, playfulness of language and the effect they bestow on literary characters etc. The current study investigates the problem of rendering PNs specifically in Children's Literature (Ch.L henceforth) and the strategic options available for the translator in order to do the job satisfactorily. First of all, the study starts with illustrating the general theoretical grounds that address the translation of PNs in Ch.L. Second, the study explicates the seven strategies proposed by the translation theorist Davies (2003). It is to be noted that the PNs chosen for the analysis in this paper are randomly- selected from different literary works due to their universality. The type of literary character chosen in this study is the protagonist around which the literary work orbits.KEY WORDS: Children’s Literature, Personal Names, Protagonists, Domestication, Foreignization, Davies' Seven strategies, culture-specific items.